Range overlap between the sword-billed hummingbird and its guild of long-flowered species: An approach to the study of a coevolutionary mosaic - Soteras, María Florencia (2018)
The coevolutionary process among free-living mutualists with extremely long matching traits may favor the formation of mutualistic interaction networks through coevolutionary escalation, complementarity and convergence. These networks may be geographically structured; the links among the species of a local network are shaped by the biotic composition of the community, thus creating selection mosaics at broader geographical scales. Therefore, to fully understand a coevolutionary process, it is crucial to visualize the geographical structure of the interaction network across the landscape. In this study we focused on the poorly known interaction system between Ensifera ensifera and its guild of long-flowered plant species. We combined occurrence data and environmental variables to predict E. ensifera distribution, in addition to range polygons available for plant species in order to evaluate the geographical variation in bill length and plant species richness. A positive relationship between bill length and plant species richness within the E. ensifera range suggests a geographical structuring of the interaction networks. At mid-latitude locations of E. ensifera range, where hummingbirds attained the longest bills, richness of long-flowered plant species was higher than at low latitude locations. These locations likely represent coevolutionary vortices where long-lasting reciprocal selection probably drove the evolution of long traits, consequently drawing new plant species into the coevolutionary network. Conversely, areas where the sword-billed hummingbird was absent or had shorter bills probably represent coevolutionary coldspots. Our results provide a first insight into this phenotypically specialized plant-pollinator network across the landscape and show candidate areas to test the predictions of the coevolutionary hypothesis, such as reciprocal selection.